Scientific publication and characteristics of the health thesis of universities in the department of Puno, Peru - Mamani-Benito, Oscar Javier (2020)
An observational cross-sectional study was conducted in order to determine the publication frequency of undergraduate health theses and identify their characteristics. The study population consisted of 482 health theses from four universities of the department of Puno approved between 2016 and 2018. Such theses belonged to the areas of medicine (25.10 %), nursing (46.5 %), nutrition (18.5 %) and psychology (10.00 %). The results show that 56.8 % of the theses used a descriptive design, 90.5 % used a non-experimental design, 36.1 % involved the hospital population and 58.70 % used a sample of 51 to 200 participants. Furthermore, only five theses (1.00 %) were published in an indexed scientific journal. It is concluded that there is a very low publication frequency of undergraduate health theses from universities of Puno, research studies use a basic design with a narrow scope and most research studies have a small sample size.